Proposta e aplicação de um modelo Hesitant Fuzzy-TOPSIS para segmentação de fornecedores - Borges, William Viana (2021)
The objective of this work is to propose a model for sustainable supplier segentation based on the segmentation approach of Rezaei and Ortt (2012) and the Hesitant Fuzzy-TOPSIS technique (BEG; RASHID, 2013). Among the contributions of this work are a systematic review of the literature on quantitative models for segmenting suppliers. Through this review, it was possible to identify some research gaps, such as the scarcity of segmentation models focused on sustainability and the lack of a decision model to support decision makers in situations of hesitation and uncertainty, in which it is preferable the use of linguistic expressions. The model proposed in this work aims to fill these research gaps and it is another contribution this present study. With the aid of Microsoft Excel © software, a computational model was developed and applied in a Brazilian Hydroelectric Powerplant. The results of this application, along with the conduction of a sensitivity analysis, indicate that the proposed model presents consistent results and it is an alternative to overcome the research gaps described above.